A Panel of High Resolution Melting (HRM) Technology-Based Assays with Direct Sequencing Possibility for Effective Mutation Screening of EGFR and K-ras Genes - D. A. M. Heideman; F. B. Thunnissen; M. Doeleman; D. Kramer; H. M. Verheul; E. F. Smit; P. E. Postmus; C. J. L. M. Meijer; G.A. Meijer; P. J. F. Snijders (Cellular Oncology)
Background: Increasing data from clinical trials support EGFR and K-ras mutation status as predictive markers of tumour response to EGFR-targeted therapies. Consequently, rapid and reliable mutation screening assays are demanded to guide rational use of EGFR-targeted therapies.